The role of bioactive compounds from Anacardium Occidentale Linn. On alpha amylase and dipeptidyl peptidase IV as antidiabetic agent for type 2 diabetes mellitus management - Abdullah Thaidi, Nur Imanina; Haron, Normah; Darnis, Deny Susanti; Mat Jusoh, Hanapi (2018)
Anacardium occidentale Linn. (A. occidentale L.) commonly known as cashew tree, is a popular tropical plant among local people and has been known to possess an excellent source of bioactive compounds. Bioactive compounds of A. occidentale L. have potency as antidiabetic for type 2 diabetes mellitus (T2DM) management. Some strategies for T2DM management are by maintaining the postprandial glucose level through the inhibition of α-amylase and by preventing the hydrolysis of Glucagon Like Peptide-1 (GLP-1) through the inhibition of Dipeptidyl peptidase IV (DPP-IV). The present study was aimed to investigate the role of bioactive compounds from A. occidentale L. in inhibiting the DPP-IV and α-amylase. HPLC-UV-Vis is used to identify and quantify the phenolic compounds present by comparing with external standards, namely, ferulic acid, p-coumaric acid, gallic acid, kaempferol and quercetin. Three fractions of maceration extracts (shoots and leaves) using methanol as solvent were undergone inhibition analysis by α-amylase assay and DPP-IV Glo protease assay. α-Amylase inhibitory activity was measured using spectrophotometric method at λ = 540 nm with acarbose as positive control. DPP-IV inhibitory activity was measured using luminescent with kaempferol as positive control. All the extracts from shoots and leaves tested revealed there were potent α-amylase and DPP-IV inhibitors, contributing to the inhibition activity significantly. Therefore, A. occidentale L. extracts could serve as a potential source to manage T2DM.